Genomic advances in the last decade and their influence in the diagnosis of intellectual disability. - Abarca Barriga, Hugo Hernán (2021)
Human intelligence is a polygenic trait (~1000 genes), with an approximate influence of 0.1% per every individual gen. It is an indispensable attribute for personal, familial, social, and economic development; furthermore, it is directly proportional to health maintenance and a longer life expectancy. Consequently, intellectual disability affects all these areas, and constitutes a public health problem in several Latin American countries where it shows a >10%. In ~85% of the patients, the etiology of intellectual disability, be that isolated or syndromic; it is mostly diagnosed through the new technological search studies of the genome, such as new generation sequencing and/or chromosomal microarray analysis. The clinical and etiological diagnosis of intellectual disability, when duly confirmed, allows the choice of specific treatment modalities, the precise determination of prognosis, and the estimation of individual or familial recurrence risks.